The impact of endovascular aneurysm repair on aortoiliac tortuosity and its use as a predictor of iliac limb complications - Coulston, James; Baigent, Amy; Selvachandran, Haran; Jones, Steven; Torella, Francesco; Fisher, Robert (Journal of vascular surgery, 2014)
Aortoiliac tortuosity is often cited subjectively as a causative factor in iliac limb complications after endovascular aneurysm repair (EVAR); however, evidence on this subject is poor. The aim of this study was to investigate the impact of stent grafting on aortoiliac tortuosity and to explore the role of the tortuosity index (TI) as a predictor of iliac limb complications after EVAR. A retrospective case-control study was performed comparing an iliac limb complication group with a control group. Reconstructed computed tomography angiography images were analyzed to calculate TI of the aortoiliac segments. This study included 153 patients, 120 in the control groups (40 Zenith flex [Cook Medical, Bloomington, Ind], 40 Endurant II [Medtronic, Minneapolis, Minn], and 40 Excluder [W. L. Gore and Associates, Flagstaff, Ariz] stent grafts) and 33 in the complications group (13 Zenith flex, 14 Endurant II, 4 Excluder, and 2 Aorfix [Lombard Medical, Oxfordshire, UK] stent grafts). There was a significant reduction in aortic and iliac TI after EVAR. This was greatest with the Zenith Flex compared with Endurant, with the least change in TI seen after Gore Excluder implantation. Iliac limb complications included 10 type Ib endoleaks, one iliac limb modular dislocation, two limbs with insufficient engagement, four occlusions, and 16 iliac limb kinks. There was no significant difference in complication rates between the three stent grafts (Zenith flex, 1.4%; Endurant, 2.9%; Excluder, 1.9%; P = .115). The median time to iliac complication was 14 months (range, 1-90 months). The iliac limb complication group was found to have a significantly increased aortoiliac TI on both preoperative and postoperative computed tomography imaging. EVAR has a significant effect on aortoiliac tortuosity. Despite the reduction of aortoiliac tortuosity after the insertion of a stent graft, TI may serve as a predictor of iliac limb complications after EVAR.